2016
DOI: 10.17221/176/2015-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Associations of reproduction and health with the performance and profit of dairy cows

Abstract: The objective of the study was to evaluate the associations of the variable intensity in culling of dairy cows and culling due to the movement disorders, mammary gland diseases, long calving interval, low fertility and postpartum complications with production, reproduction and economic parameters on 60 commercial dairy herds. The data encompassed 34 632 cow records from the Czech Republic 12 regions and were collected during a 1-yr period (2012). The milk yield during the production period was analysed relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…According to Stone et al (2017) the neck activity would likely increase due to more frequent visits to the feed bunk by highyielding cows. As noted by Krpalkova et al (2016), animals have certain biological limits and any disruption of homeostasis in their bodies leads to difficulties in their future performance. According to Beauchemin (2018) the process of rumination plays a vital role; cows can voluntarily control their rumination and stop ruminating when disturbed or experiencing some discomfort (e.g.…”
Section: Rt As a Reflection Of Body Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Stone et al (2017) the neck activity would likely increase due to more frequent visits to the feed bunk by highyielding cows. As noted by Krpalkova et al (2016), animals have certain biological limits and any disruption of homeostasis in their bodies leads to difficulties in their future performance. According to Beauchemin (2018) the process of rumination plays a vital role; cows can voluntarily control their rumination and stop ruminating when disturbed or experiencing some discomfort (e.g.…”
Section: Rt As a Reflection Of Body Conditionmentioning
confidence: 99%
“…Stone et al (2017) added that cows with greater MY have higher nutrient requirements and may spend more time on feed consumption and rumination. Krpalkova et al (2016) reported that some herds with high overall culling rate due to several illnesses had high milk yield performance. It means that the high-yielding cow may have a high milk yield and be profitable, but at the same time, the cow must maintain the healthy body condition.…”
Section: Rt As a Reflection Of Body Conditionmentioning
confidence: 99%
“…The primary cause of reproductive challenges in dairy cattle often stems from the subfertility or infertility of the breeding bulls (Fair & Lonergan, 2018, Taylor et al, 2018 [5,24] . The overall profitability of a herd is directly linked to the reproductive efficiency or inefficiency of the bulls (Krpalkova et al, 2016) [9] . Thus, it is essential to assess semen quality before performing Artificial Insemination (AI) to prevent reproductive failures, especially considering that semen from one bull is used for inseminating multiple cows.…”
Section: Introductionmentioning
confidence: 99%
“…It is the first actual barrier when a pathogenic agent enters the body, and it is on the state of this factor that the health and wellbeing of the herd depends. Adverse effect on animal body is reflected in hematological profile, indicators of which indicate state of nonspecific resistance of organism [10]. In this regard, special preventive and therapeutic methods should be used, certain veterinary and hygienic conditions of maintenance and operation, as well as animal feeding standards should be observed [11].…”
Section: Introductionmentioning
confidence: 99%